Substance Abuse, Depression, and Social Anxiety: Case Study and Application of Cognitive Psychotherapy - Abu Al-Khair, Feda (Case Reports in Psychiatry, 2023)
A 20-year-old male was referred by a psychiatrist to the clinic for treatment. He was diagnosed with social anxiety disorder (SAD), depression, and substances abuse. He complained of depressive mood and severe anxiety symptoms. These symptoms are triggered in social situations, as well as when talking to others, being in public areas, and going to malls or any crowded places. Because of his symptoms, he avoided getting into the situation, which affected his daily life. The patient was diagnosed with SAD, major depression, and substance abuse and underwent 20 separate sessions of cognitive behavioral therapy (CBT). The application of CBT led to a decrease in the number of anxiety attacks and angry outbursts that the patient suffers from. It also helped him learn some techniques to use in his interactions within the society, as well as other techniques, such as cognitive reorganization of dysfunctional thoughts, and gradually exposed him to the social situations. He also learned to practice some relaxation techniques, to teach him integration in social situations and confrontation instead of avoidance.